Patterns and trends in contraceptive use among women attending Title X clinics and a national sample of low-income women()() - Fowler, Christina I. (Contracept X, 2019)
OBJECTIVES: To describe the types of contraception used by women attending Title X-funded clinics and a comparable group of low-income reproductive-age women at risk of unintended pregnancy. STUDY DESIGN: We estimated the percentage of reproductive aged (15–44 years) women using contraception, by method type and level of effectiveness in preventing pregnancy (i.e., most, moderately, and less effective), using Title X Family Planning Annual Report (2006–2016) and National Survey of Family Growth (2006–2015) data. We divided most effective methods into permanent (female and male sterilization) and reversible (long-acting reversible contraceptives [LARCs]) methods. RESULTS: Among Title X clients during 2006–2016, use of LARCs increased (3–14%); use of moderately effective methods decreased (64–54%); and use of sterilization (~ 2%), less effective methods (21–20%), and no method (8–7%) was unchanged. These same trends in contraceptive use were observed in a comparable group of women nationally during 2006–2015, during which LARC use increased (5–19%, p < .001); moderately effective method use decreased (60–48%, p < .001); and use of sterilization (~5%), less effective methods (19%), and no method (11–10%) was unchanged. CONCLUSIONS: The contraceptive method mix among Title X clients differs from that of low-income women at risk of unintended pregnancy nationally, but general patterns and trends are similar in the two populations. Research is needed to understand whether method use patterns among low-income women reflect their preferences, access, or the conditions of the supply environment. IMPLICATIONS: This study contributes to our understanding of patterns and trends in contraceptive use among two groups of reproductive-age women — Title X clients and low-income women nationally who are at risk of unintended pregnancy. The findings highlight areas for further research.